1996
DOI: 10.2165/00002018-199614020-00004
|View full text |Cite
|
Sign up to set email alerts
|

Nimesulide in the Treatment of Patients Intolerant of Aspirin and other NSAIDs

Abstract: Aspirin (acetylsalicylic acid) and other NSAIDs are responsible for many adverse effects. Among them, pseudo-allergic reactions (urticaria/angioedema, asthma, anaphylaxis) affect up to 9% of the population and up to 30% of asthmatic patients. The mechanisms provoking these reactions have not been fully elucidated, but it appears that inhibition of cyclo-oxygenase (COX) plays a central role. The anti-inflammatory action of nimesulide differs from that of other NSAIDs, possibly because of its chemical structure.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 46 publications
1
13
0
Order By: Relevance
“…Data from the Spanish Pharmacovigilance System reported a higher rate of hepatic injury with nimesulide than with other NSAIDs during the 1990s (Maciá et al, 2002) At therapeutic doses, nimesulide does not appear to precipitate asthma in NSAID-sensitive asthmatics. This supports the concept that aspirin-induced asthma is caused by inhibition of COX-1 (Bianco et al, 1993;Senna et al, 1996;Gryglewski, 1998;Bennett, 2000). Prolonged treatment with nimesulide has delayed premature labor for up to 34 weeks without serious fetal side effects and resulted in a successful delivery (Sawdy et al, 1997).…”
Section: A Treatment Of Inflammatory Diseasessupporting
confidence: 59%
“…Data from the Spanish Pharmacovigilance System reported a higher rate of hepatic injury with nimesulide than with other NSAIDs during the 1990s (Maciá et al, 2002) At therapeutic doses, nimesulide does not appear to precipitate asthma in NSAID-sensitive asthmatics. This supports the concept that aspirin-induced asthma is caused by inhibition of COX-1 (Bianco et al, 1993;Senna et al, 1996;Gryglewski, 1998;Bennett, 2000). Prolonged treatment with nimesulide has delayed premature labor for up to 34 weeks without serious fetal side effects and resulted in a successful delivery (Sawdy et al, 1997).…”
Section: A Treatment Of Inflammatory Diseasessupporting
confidence: 59%
“…Several reviews have been published in recent years on the adverse reaction profi le of nimesulide in comparison with that of other NSAIDs (Rainsford, 1996(Rainsford, , 1998(Rainsford, , 1999b(Rainsford, , 2001Bianco et al, 1993;Senna et al, 1996;Conforti et al, 2001;Lanas 2001;Boelsterli, 2002aBoelsterli, , 2000bTraversa et al, 2003;Laporte et al, 2004). These studies show that nimesulide has, overall, a pattern of organ reactions similar to that from other NSAIDs, though there are quantitative differences in the incidence of adverse reactions.…”
Section: Adverse Reactions and Relative Safetymentioning
confidence: 97%
“…A particular advantage in the respiratory conditions is the relatively low likelihood of asthmatic and other allergic reactions with nimesulide (Bianco et al, 1993, Senna et al, 1996Bianchi et al, 2005).…”
Section: Headache Ent Infections Fever and Minor Pain Statesmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, nimesulide seems safe to use in aspirin sensitive asthmatic patients. Several recent studies in NSAID intolerant asthmatic patients have shown that therapeutic doses of nimesulide did not induce asthmatic attacks while high doses of 400 mg only precipitated mild asthma in 10% of patients 77. Perhaps aspirin induced asthma is associated with COX-1 inhibition?…”
Section: Selective Inhibition Of Cox-2mentioning
confidence: 99%